2018
DOI: 10.1177/0146167218791782
|View full text |Cite
|
Sign up to set email alerts
|

Do You See What I See? Actor and Partner Attachment Shape Biased Perceptions of Partners

Abstract: The present research examined how actor and partner attachment insecurity relates to biases in perceptions of partners' core relationship-relevant constructs. Across three dyadic studies ( N = 333, N = 666), we examined attachment anxiety and avoidance as predictors of over- or underestimation of partners' relationship satisfaction, commitment, and responsiveness, using partners' own reports as the reference point for evaluating bias. Actors higher in avoidance and actors with partners higher in avoidance perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“… Note : Deviations from what was reported in the registered report are highlighted in italics. These include the following: a) in Rodriguez et al (2019), there were hypotheses for the effects of partner attachment on responsiveness discrepancies that were not extracted or preregistered for analysis; b) changing reporting from partially standardized estimates for the discrepancy outcomes in the original data extracted from Rodriguez et al (2019) to fully standardized estimates; and c) adjusting estimates and p ‐values for several erroneously extracted original studies. None of these changed the sign nor significance of estimates with the exception of H2B from Study 2 of Nguyen et al (2018), which was originally reported as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Note : Deviations from what was reported in the registered report are highlighted in italics. These include the following: a) in Rodriguez et al (2019), there were hypotheses for the effects of partner attachment on responsiveness discrepancies that were not extracted or preregistered for analysis; b) changing reporting from partially standardized estimates for the discrepancy outcomes in the original data extracted from Rodriguez et al (2019) to fully standardized estimates; and c) adjusting estimates and p ‐values for several erroneously extracted original studies. None of these changed the sign nor significance of estimates with the exception of H2B from Study 2 of Nguyen et al (2018), which was originally reported as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 15 eligible research items, 7 items were unique (i.e., the other 8 were overlapping: for instance, a finding that was both presented as a poster and published in a manuscript). The seven research items, in turn, contributed 116 dyadic cross-sectional estimates from 12 separately reported studies (Baker, Chopik, & Nguyen, under review;Baker, Nguyen, Knee, & Petit, 2018;Haddad et al, 2016;Hadden, Baker, & Knee, 2018;Hadden, Rodriguez, Knee, DiBello, & Baker, ;Rodriguez et al, 2019).…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with previous research (e.g., Gable, 2006;Kuster et al, 2015;Pusch et al, 2020;Sanderson & Cantor, 2001;Strachman & Gable, 2006), we expected a strong explicit desire for closeness and a strong pnCommunion Approach to be associated with an overestimation, and a strong pnCommunion Avoidance to be associated with an underestimation of the partner's communal motives (as indicated by positive and negative bias effects, respectively). We addressed our hypotheses with Actor-Partner Interdependence Models (Kenny et al, 2006) which are well established and widely used in research on partner perception (e.g., Campbell et al, 2013;Clark et al, 2017;Kenny & Acitelli, 2001;Rodriguez et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%